The genome sequence of black horehound, Ballota nigra L. subsp. foetida (Lam.) Hayek (Lamiaceae) [version 1; peer review: 2 approved] - Maarten J. M. Christenhusz; Ilia J. Leitch; Michael F. Fay (Wellcome Open Research)
We present a genome assembly from a specimen of Ballota nigra (black horehound; Tracheophyta; Magnoliopsida; Lamiales; Lamiaceae). The genome sequence is 1186.8 megabases in span. Most of the assembly is scaffolded into 11 chromosomal pseudomolecules. Three mitochondrial chromosomes were assembled, with lengths of 148,17, 121,67 and 125,74 kilobases. The chloroplast genome has been assembled and is 151.91 kilobases in length.